Quasi-2D simulation of soya beans flow in mixed flow dryer. (December 2020) - Lorenzoni, Ricardo K.; Binelo, Manuel O.; Khatchatourian, Oleg; Ziganshin, Bulat G.; de F. B. Binelo, Marcia
Abstract: The production of soya is very important for the global food security, and the drying process exerts great impact on grain quality. The irregular flow of the grain in a mixed flow dryer can produce a non-uniform drying of the grains. The objectives of this work were to verify the suitability of the use of the discrete element method simulations in a quasi-two-dimensional domain, to perform experiments with the objective of validating the results found in the simulations, and to analyse the main aspects of grain flow in a mixed flow dryer. The software YADE was used in the simulations, and the results obtained by the quasi-2D simulations were similar to those obtained in the 3D case, using considerable less computational resources. The simulations of soya beans flow in MFD show that particle size does not affect the residence time, when considering the typical soya beans size variation. Simulations carried out considering different moisture content values show that residence time increases with moisture content. The results also show that porosity distribution is not uniform, which can impact airflow mathematical models. Highlights: Experiments with soya bean flow were carried out. Quasi-2D and 3D simulations of the experimental apparatus using DEM were made. Quasi-2D simulations based on mixed flow dyer were made. Relative residence time of grains were obtained using quasi-2D simulations.